Optimizing Digital Literacy Integration in Early Childhood Education: A Case Study of Tarbiyatul Athfal Bulumanis Kidul Kindergarten - Tafrihah; Utanto, Yuli; Pristiwati, Rahayu (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
Digital literacy is increasingly recognized as a fundamental component of early childhood education, equipping young learners with essential skills to navigate digital environments. This study investigates the implementation of digital literacy in the independent curriculum at Tarbiyatul Athfal Bulumanis Kidul Kindergarten, focusing on organizational strategies, challenges, and pedagogical impacts. Employing a qualitative case study approach, data were gathered through observations, semi-structured interviews, and document analysis involving key stakeholders such as teachers, curriculum coordinators, and administrators. The findings indicate that while educators possess foundational digital competencies, continuous professional development is required for effective technology integration. Infrastructure limitations, financial constraints, and technical difficulties remain significant barriers to optimal digital literacy adoption. However, structured pedagogical strategies that incorporate information and communication technology (ICT) have been shown to enhance student engagement and learning outcomes. The study underscores the necessity of robust teacher training programs, improved digital infrastructure, and multi-stakeholder collaboration to ensure the sustainable integration of digital literacy in early childhood education. A key finding reveals that despite existing challenges, schools that implement digital literacy with structured teacher support and adaptive learning strategies demonstrate significant improvements in students' digital competencies and cognitive engagement. Future research should explore the long-term effects of early digital literacy exposure on cognitive and social development across diverse educational settings.